Pembuatan Bentonit Terpilar Al Dari Bentonit Alam Blang Karing Untuk Peningkatan Daya Serap Ion Logam Berat Pb Dan Cd - Muhammad Ridha Cessar; Muhammad Syukurdi; Jakfar Jakfar; Hisbullah Hisbullah (Jurnal Inovasi Ramah Lingkungan, 2021)
Waste Pb are waste derived from human activities. One way to reduce this problem by adsorption through bentonite. In this research bentonite used originated from Blang Karing, Aceh. The bentonite is activated into sodium bentonite and is enlarged with Al to become Al-Pillared bentonite. Variation of metal concentration used are 300, 400, 500, and 600 ppm mixed with bentonite. Afterwards the mixture was filtered and the filtrate was taken to analyze the remaining metal content with AAS. This study showed that the greater the amount of adsorbate concentration used, the absorption of bentonite will also be greater. The amount of metal Pb and Cd left behind with initial concentration of 300 ppm respectively is 299,624 ppm (99.87%) and 289,813 ppm (96.60%). In the usage of adsorbate concentration of 600 ppm the amount of metal Pb and Cd left behind respectively is 599,605 ppm (99.93%) and 588,464 ppm (98.08%). 2+ and Cd 2+